Viewpoints of Faculty Members and Residents of Kerman University of Medical Sciences Iran Regarding the Local Annual Upgrade and Licensure Residency Exams - Elham Iranmanesh; Ali Hosseininasab; Ali Hosseininasab; Alireza Shahidi (Kerman University of Medical Sciences, 2017)
Background & Objective: In the past the written exam for the promotion and certification of medical residents was provided nationwide and conducted by the Council of Graduate Medical Education Changes in the method of performing medical residents promotion exams have been continuously discussed by scholars According to the educational approach in the prestigious universities of the world in the field of specialized clinical residency training the promotion exam has been transferred to residents training universities In this study the viewpoints of faculty members and residents of Kerman University of Medical Sciences Iran were evaluated regarding the decentralized promotion and certification residency exam Methods: This was a crosssectional study The study population consisted of all residents and faculty members of Kerman University of Medical Sciences The data were collected using a selfadministered questionnaire including questions about the strengths and weaknesses of the decentralized residency upgrade and certification exam Data were analyzed using SPSS software All Pvalues of ≤ 005 were considered significant Results: The items of "participation of all members of the department in questions preparation" and "more attention to the endemic diseases" (score of 406 and 355 respectively) obtained the highest scores The lowest dispersion rate was also related to these two components The item "decreased quality of questions" with a score of 245 had the lowest impact From the viewpoint of faculty members "participation of all members of the department in questions preparation and different education due to different assessment methods in universities (376 and 375 respectively) obtained the highest scores Moreover "bias in the ministries regarding enrichment of question banks" and "closure of departments during questions preparation" obtained the lowest scores (285) There was no significant difference between the two groups in scoring of the components based on demographic characteristics Conclusion: Although in the view of residents and faculty members the decentralization of this exam has some benefits there are many deficiencies which must be addressed in order to attain greater effectiveness